Amelioration of Endothelial Dysfunction in Diabetes: Role of Takeda G Protein–Coupled Receptor 5 - Cai, Zhengyao; Yuan, Suxin; Zhong, Yi; Deng, Li; Li, Jiafu; Tan, Xiaoqiu; Feng, Jian (Frontiers in Pharmacology, 2021)
Diabetes mellitus (DM) eventually leads to chronic vascular complications, resulting in cardiovascular diseases. DM-associated endothelial dysfunction (ED) plays an important role in the development of chronic vascular complications. Low endothelial nitric oxide synthase(eNOS) activity, inflammation, and oxidative stress all contribute to this ED. The G protein-coupled receptor Takeda G protein-coupled receptor 5 (TGR5) is a membrane receptor for bile acids that plays an important role in the regulation of glucose metabolism. Recent studies have shown that TGR5 is involved in the regulation of various mediators of ED, which suggests that TGR5 may represent a target for the treatment of DM-associated ED. In this review, we summarize the principal mechanisms of DM-associated ED, then propose TGR5 as a novel therapeutic target on the basis of its mechanistic involvement, and suggest potential directions for future research.